IMPACT OF HEALTHCARE KNOWLEDGE MANAGEMENT ON THE STRATEGIC POSITION OF HOSPITALS: AN ANALYTICAL STUDY - Mahdi, Dalal Salih; Madlool, Jaleel Kadhim (PEOPLE: International Journal of Social Sciences, 2021)
Healthcare knowledge management HKM has attracted extensive attention in the previous years as a strategical partner with the general strategy of organizations. The HKM aims to identify the organization strategic position within the competitive market. The present study tries to answer many questions that formed the study problem including do hospitals and health units depend on the healthcare knowledge storage to perform its strategical tasks and how to run this healthcare knowledge; does the healthcare knowledge transformation represent the main base to attain these especial strategic tasks by identifying its strategic position. A virtual form has been proposed that reflects the interaction relation nature between variables. The virtual form is clarified by the study's main assumption which was tested using data obtained from surveys and other different data collecting methods about different Iraqi hospitals and health units. The study highlighted the significant role of the HKM in hospitals and health units. Also, it was found that the Iraqi hospitals and health units have a growing interest to diagnose its weaknesses to build a strong internal environment. The present study recommends holding training courses continuously to improve the staff’s abilities. In addition, the study recommends establishing environmental analysis units to study and evaluate environmental changes.